(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
In this article, the prevalence of helminthiasis among 1st to 3rd-grade students of secondary schools in the Kasbi and Karshi districts of the Kashkadarya region was studied. Within the framework of the research, a total of 1,850 students from 24 schools underwent laboratory and epidemiological examinations. Analysis revealed significant differences between the regions: it was found that 17.7% of students in the Kasbi district and 26.2% in the Karshi district were infected with parasitic diseases. The article provides a structural analysis according to the types of helminthiasis identified. In both regions, hymenolepiasis (dwarf tapeworm) occupies the leading position; however, the higher incidence of taeniarhynchosis and ascariasis in the Karshi district indicates the need to strengthen food safety and sanitary control in the area. During the study, the hygienic conditions in schools and the level of children’s sanitary culture were also investigated, and based on the results, practical recommendations aimed at reducing the level of invasion among school-aged children were developed.